2014
DOI: 10.2147/nrr.s70216
|View full text |Cite
|
Sign up to set email alerts
|

The lived experience of neophyte nursing instructors: mentorship and its role in their development

Abstract: Numerous studies have identified the need for the mentorship of nursing instructors, yet there is a gap in literature identifying outcomes of successful mentorship programs. The purpose of this phenomenological inquiry was to uncover the lived experience of neophyte nursing instructors and the essence of the phenomenon of mentorship. Data were collected through individual interviews with six neophyte nursing instructors. Interviews were audio-taped and transcribed verbatim. Data were analyzed using a phenomeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Studies were conducted in Canada ( n = 4), Australia ( n = 2) and the USA ( n = 28) and captured diverse populations in nursing academia (mentors, mentees, nursing instructors, faculty and administration). Sample sizes ranged from 6 (Nowell , Terry )‐959 participants (Chung & Kowalski ). Several studies were conducted to evaluate specific mentorship programmes (Matthew‐Maich et al .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies were conducted in Canada ( n = 4), Australia ( n = 2) and the USA ( n = 28) and captured diverse populations in nursing academia (mentors, mentees, nursing instructors, faculty and administration). Sample sizes ranged from 6 (Nowell , Terry )‐959 participants (Chung & Kowalski ). Several studies were conducted to evaluate specific mentorship programmes (Matthew‐Maich et al .…”
Section: Resultsmentioning
confidence: 99%
“…Confidence 5/0 (Taylor 1992, Hill 2004, Matthew-Maich et al 2007, Cannon 2014, Nowell 2014 Decreased anxiety 1/0 (Nowell 2014) Psychological empowerment 1/0 (Chung & Kowalski 2012) Desire to mentor 5/1 (Butler 1990, Torsella 1994, Hill 2004, Nowell 2014, Silao 2015) (Butler 1990) These data are insufficient to suggest causality of mentorship on the identified outcomes. The review revealed an absence of experimental research about mentorship in nursing academia and established the current state of evidence.…”
Section: Psychosocial-relatedmentioning
confidence: 99%
See 2 more Smart Citations
“…The mentoring role included providing helpful tips about clinical teaching practice and collegial guidance and support for the new instructors for the duration of the term. The mentor-mentee dyad model as described by Nowell was used [20]. This model ensured that mentees were paired with mentors according to their similar specialties so mentors could answer pertinent questions and provide adequate guidance to the mentees about how to perform their clinical instructor role tasks.…”
Section: Participantsmentioning
confidence: 99%